Development and validation of analytical method for the estimation of nateglinide in rabbit plasma - Nihar Ranjan Pani; Lilakant Nath; Akhilesh Vikram Singh; Santosh Kumar Mahapatra (Elsevier, 2012)
Nateglinide has been widely used in the treatment of type-2 diabetics as an insulin secretogoga. A reliable, rapid, simple and sensitive reversed-phase high performance liquid chromatography (RP-HPLC) method was developed and validated for determination of nateglinide in rabbit plasma. The method was developed on Hypersil BDSC-18 column (250Â mmÃ4.6Â mm, 5Â mm) using a mobile phase of 10Â mM phosphate buffer (pH 2.5) and acetonitrile (35:65, v/v). The elute was monitored with the UVâvis detector at 210Â nm with a flow rate of 1Â mL/min. Calibration curve was linear over the concentration range of 25â2000Â ng/mL. The retention times of nateglinide and internal standard (gliclazide) were 9.608Â min and 11.821Â min respectively. The developed RP-HPLC method can be successfully applied to the quantitative pharmacokinetic parameters determination of nateglinide in rabbit model. Keywords: HPLC, Nateglinide, Rabbit plasma, Pharmacokinetics